2017
DOI: 10.1117/1.oe.56.3.031221
|View full text |Cite
|
Sign up to set email alerts
|

Dual-polarization airborne lidar for freshwater fisheries management and research

Abstract: Abstract. The design of a compact, dual-polarization, nonscanning lidar system intended to fly in a small, singleengine aircraft for airborne study of freshwater marine ecosystems and mapping of fish schools in mountain lakes is discussed. Design trade-offs are presented with special attention paid to selecting the field of view and telescope aperture diameter. Example results and a comparison with a similar existing lidar system are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 55 publications
0
10
0
2
Order By: Relevance
“…Since the first recorded detection of fish by airborne lidar in 1976 (Squire and Krumboltz, 1981), a number of studies have shown that lidar compares well with traditional techniques for fish in the upper 30-40 m of the water column (Churnside et al, 2003(Churnside et al, , 2017bRoddewig et al, 2017). The advantage of airborne lidar for fisheries surveys is that it can cover large areas quickly and at lower cost than a surface vessel.…”
Section: Polarization Lidarmentioning
confidence: 99%
“…Since the first recorded detection of fish by airborne lidar in 1976 (Squire and Krumboltz, 1981), a number of studies have shown that lidar compares well with traditional techniques for fish in the upper 30-40 m of the water column (Churnside et al, 2003(Churnside et al, , 2017bRoddewig et al, 2017). The advantage of airborne lidar for fisheries surveys is that it can cover large areas quickly and at lower cost than a surface vessel.…”
Section: Polarization Lidarmentioning
confidence: 99%
“…Nowadays airborne hydrooptical lidars are used for solving a wide range of bathymetric problems [1-4], search of fish schools [5][6][7], detection of oil films on the sea surface [8,9], and estimation of the plankton concentration in subsurface layers of the ocean [10,11]. Airborne lidars are widely used to obtain depth profiles of optical sea water characteristics, such as the extinction, backscattering, and absorption coefficients of laser radiation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…LiDAR remote sensing has the advantage of range-resolved and deeper penetration, hence providing vertical structure information, which could provide a good supplement to passive remote sensing [2]. Increasingly, LiDAR has more and more applications, including bathymetric survey [3,4] and optical profiling of water columns [5][6][7][8], also for detecting plankton scattering layers [9][10][11], bubbles [12], internal waves [13], schools of fish [14,15], and so on. However, there are no publications on using airborne LiDAR to estimate the optical property profiles in the South China Sea (SCS) so far.…”
Section: Introductionmentioning
confidence: 99%